Biocompatible polymeric microparticles produced by a simple biomimetic approach - Costa, A. M. S. (2014)
The use of superhydrophobic surfaces to produce polymeric particles proves to be biologically friendly since it entails the pipetting and subsequent cross-linking of polymeric solutions under mild experimental conditions. Moreover, it renders encapsulation efficiencies of ∼100%. However, the obtained particles are 1 to 2 mm in size, hindering to a large extent their application in clinical trials. Improving on this technique, we propose the fabrication of polymeric microparticles by spraying a hydrogel precursor over superhydrophobic surfaces followed by photo-cross-linking. The particles were produced from methacrylamide chitosan (MA-CH) and characterized in terms of their size and morphology. As demonstrated by optical and fluorescence microscopy, spraying followed by photo-cross-linking led, for the first time, to the production of spherical particles with diameters on the order of micrometers, nominal sizes not attainable by pipetting. Particles such as these are suitable for medical applications such as drug delivery and tissue engineering.